Incorporating oral health collaborative practice into primary medical care in Ireland - AHERN, JOHN MARTIN (Trinity College Dublin. School of Medicine. Discipline of Public Health & Primary Care, 2019)
Aim: The aim of this study was to explore the opportunities for, and the barriers to, the integration of oral health into primary health care in Ireland, and to propose recommendations to support the development of sustainable collaborative practice relationships between primary care medical and dental professionals. Materials and Methods: This thesis consists of both qualitative and quantitative methodologies. There were three parts to this study, Parts A-C. Part A consisted of a qualitative semi-structured interview study to explore dentist?s views on incorporating oral health collaborative practice into primary medical care in Ireland. Part B consisted of a cross-sectional online survey study of GPs in Ireland, to determine the confidence and willingness of GPs to incorporate oral health as part of routine diabetes care, by examining current oral health knowledge, interest and practices, in addition to their experience of and attitudes towards oral health education. Part C consisted of a retrospective analysis to examine the way in which malignant and potentially malignant oral lesions are first detected in the primary care setting in Ireland, by reviewing the clinical notes to determine which health professional first detected the oral lesion, and whether the lesion was detected as a presenting complaint, or as an opportunistic finding. Results: In Part A, dentists perceived a lack of interest in oral health among medical professionals and suggested both a paucity of oral health education and competing systemic health priorities as reasons for this perception. In Part B, results showed that GPs are interested in oral health. However, results showed that GPs received very little oral health education at either the undergraduate or postgraduate levels. In Part A, dentists also believed that patients have poor oral health knowledge and that many patients preferentially attend their GP for oral health problems, especially soft tissue problems. In Part B, GPs reported that patients do often consult their opinion regarding oral health symptoms, especially symptoms related to the oral soft tissues. In Part C, the vast majority of oral cancers self-presented to GPs at an advanced stage. Conversely, a significant amount of early asymptomatic potentially malignant oral lesions was detected opportunistically by dentists (OR 7.82; 95% CI (2.67,22.94)). In Part A, dentists believed that GPs could play a major role in oral disease prevention by identifying shared risk factors for oral disease, by promoting oral health and by facilitating referral to a dentist. In Part A, dentists identified the early detection of oral cancer in primary care and improving chronic systemic disease management, especially for patients with diabetes, to be the two areas where GPs may have greatest potential to play an important role in oral health collaborative practice. However, both GPs and dentists report poor communication with one another. For example, in Barriers to collaborative practice were identified throughout the different parts of this study. In Part A, dentists reported poor communication with GPs. In Part B, poor communication was also identified as a barrier. For example, the majority of GPs surveyed never (58%) or rarely (35%) refer their patients with diabetes to attend a dentist as part of overall diabetes care. However, the vast majority of GPs surveyed (82%) reported often referring their patients with diabetes to other health professionals as part of overall diabetes care. Conclusion: This study revealed an absence of a culture of collaborative practice between medical and dental professionals in the primary care setting in Ireland. This was evidenced by the reportedly poor level of communication, the paucity of referrals between each other and the perceived separation from one another in the health care team. Specific opportunities for oral health collaborative practice were identified, and both GPs and dentists in this study identified feasible goals for collaborative practice around these perceived opportunities. However, a number of challenges to the successful incorporation of oral health collaborative practice were identified; notably in the areas of education, health care services, policy and practice. Based on the findings of this study, this thesis concluded with recommendations to address the aforementioned challenges in the areas of education, health care services, policy and practice.
APPROVED
Keywords: oral health; primary care; integrated care; interprofessional education; collaborative practice